2022
DOI: 10.1111/ejn.15590
|View full text |Cite
|
Sign up to set email alerts
|

Common principles in the lateralization of auditory cortex structure and function for vocal communication in primates and rodents

Abstract: This review summarizes recent findings on the lateralization of communicative sound processing in the auditory cortex (AC) of humans, non‐human primates and rodents. Functional imaging in humans has demonstrated a left hemispheric preference for some acoustic features of speech, but it is unclear to which degree this is caused by bottom‐up acoustic feature selectivity or top‐down modulation from language areas. Although non‐human primates show a less pronounced functional lateralization in AC, the properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 252 publications
0
4
0
Order By: Relevance
“…Research in mice has begun to identify neuromodulators and genes that facilitate this experience‐dependent plasticity that accompanies the learning of maternal behavior, including the hormones oxytocin and estradiol, as well as the gene MECP2 10,70–72 . Furthermore, a subset of this study has demonstrated that left A1 in particular shows lateralization of pup vocalization perception in experienced mothers, which suggests a possible parallel to the left lateralization of human vocal perception and social communication 10,58,66,73,74 . This lateralization may be due, in part, to the observed distribution of oxytocin receptors favoring left A1 10,75 .…”
Section: Cues Eliciting Parental Behavior: Auditionmentioning
confidence: 66%
See 1 more Smart Citation
“…Research in mice has begun to identify neuromodulators and genes that facilitate this experience‐dependent plasticity that accompanies the learning of maternal behavior, including the hormones oxytocin and estradiol, as well as the gene MECP2 10,70–72 . Furthermore, a subset of this study has demonstrated that left A1 in particular shows lateralization of pup vocalization perception in experienced mothers, which suggests a possible parallel to the left lateralization of human vocal perception and social communication 10,58,66,73,74 . This lateralization may be due, in part, to the observed distribution of oxytocin receptors favoring left A1 10,75 .…”
Section: Cues Eliciting Parental Behavior: Auditionmentioning
confidence: 66%
“…10,[70][71][72] Furthermore, a subset of this study has demonstrated that left A1 in particular shows lateralization of pup vocalization perception in experienced mothers, which suggests a possible parallel to the left lateralization of human vocal perception and social communication. 10,58,66,73,74 This lateralization may be due, in part, to the observed distribution of oxytocin receptors favoring left A1. 10,75 Altogether, the auditory system presents itself as an attractive entry point into the adaptive parental brain.…”
Section: Cues Eliciting Parental Behavior: Auditionmentioning
confidence: 99%
“…This asymmetry is not present in chimpanzees (see review 30 ). A larger spacing between minicolumns equals a larger amount of neuropil, which, in turn, represents a higher number of dendrites, axon terminals, and synapses, allowing for more refined processing by the minicolumns [31][32][33] .…”
Section: Planum Temporalementioning
confidence: 99%
“…The auditory system exhibits a plethora of hemispheric lateralisations in both structure and function (for a review, see Ruthig & Schönwiesner, 2022; Ocklenburg & Güntürkün, 2024). In humans, language processing serves as a prime example, as it was originally thought to reside predominantly in the left hemisphere (Broca, 1861; Wernicke, 1874).…”
Section: Introductionmentioning
confidence: 99%